Prediction of the Soil Lost Amount using the Revised Universal Soil Loss Equation (RUSLE), Geographic Information System and Remote Sensing in Wadi Ibn Hammad basin/Al-Karak Governorate - Zregat, Dalal; Alzghoul, Maysoon (Dirasat: Human and Social Sciences, 2021)
This study aims to predict the quantities of soil lost by the water erosion in wadi Ibn Hammad basin area (120.54 km²), southern Jordan using analytical, descriptive approaches, Revised universal Soil Loss Equiation (RUSLE), Geographic Information system (GIS) and remote sensing techniques (RS) Different topographic characteristics through Digital Elevation Model (DEM), derived from the topographic maps of Wadi Ibn Hammad, scale 1: 50000, and the Landsat satellite for the year 2018. R factor was calculated through mathematical equation after collecting rain data from weather station, k value of each soil sample was calculated after determination of texture, structure ,saturated hydrolic conductivity, and organic matter).a map were prepared Showed local distribution of k values .slop factor was determined as well as using DEM for Studied region, and slop map was introduced in mathematical equation through a GIS to obtain LS map .NDVI used for studied region to calculate C map. To obtain predictive map of soil lost quantities, maps of LS, C, K was multiplicities with R value. The results showed that R value in studied region 75-325, while k factor value was 0.03-0.3.soil with low value concentrated at medium part of studied region, while slop Factor value was between 0-3.C factor value was 0.33-.99. P factor value was 0.55-1 .The results of soil lost quantities were classified in to 4 Classes in studied region: low (0-48) t/h/year, and medium (49-96) t/h/y, and severe in which soil loss exceeded 97-199 t/h/year, extreme 200-240 t/h/y.